2007
DOI: 10.1016/j.jmhg.2007.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone and the brain

Abstract: The effects of testosterone on sexual appetite are obvious. Furthermore, treatment of hypogonadal men with testosterone leads almost always to unmistakable positive changes in mood, self-esteem and vitality. This testifies to the profound effects testosterone exerts on the brain and the mind. Conversely, hypogonadism and particularly the profound hypogonadism resulting from androgen deprivation treatment in men with prostate cancer, is associated with loss of vitality and mood disorders, if not depression. Sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…In addition to these structural effects, the amount of circulating ovarian hormones influenced functional abilities in humans, specifically, verbal memory ( Peper et al, 2011 ) and explicit memory recall ( Gooren, 2007 ). Moreover, estrogen administration was found to protect against neurodegeneration only in cognitively intact women for whom degeneration had not yet started ( Siegfried, 2007 ).…”
Section: Estrogen and Testosterone: Aging Cognition And Socioemotiomentioning
confidence: 99%
“…In addition to these structural effects, the amount of circulating ovarian hormones influenced functional abilities in humans, specifically, verbal memory ( Peper et al, 2011 ) and explicit memory recall ( Gooren, 2007 ). Moreover, estrogen administration was found to protect against neurodegeneration only in cognitively intact women for whom degeneration had not yet started ( Siegfried, 2007 ).…”
Section: Estrogen and Testosterone: Aging Cognition And Socioemotiomentioning
confidence: 99%
“…The relationship between brain and the endocrine system is currently more widely understood. Brain contains receptors for androgens and estrogens, being capable of synthesizing and metabolizing these steroids, while hormones impact on neurotrophic factors and effect cognitive behavior [14]. Gonadal steroid hormones become elevated during puberty, sculpting the adolescent brain in both females and males.…”
Section: Introductionmentioning
confidence: 99%
“…Gonadal steroid hormones become elevated during puberty, sculpting the adolescent brain in both females and males. Furthermore, it has been recognized that the actions of pubertal hormones during adolescence may have long-lasting consequences [15], while there is also evidence of a role of testosterone on cognition [14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, degenerative process was going on inspite of testosterone therapy. According to Gooren (2007), the duration of hypogonadism affects the efficacy of testosterone substitution. Eriksson et al (1998) stated that loss of neurons is thought to be irreversible in the adult human brain, which is the cause of neurological disease and impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have reported no benefit with testosterone substitution, others have found significant improvement in orientation and memory. Accordingly, many authors postulated that further investigation of the effects of testosterone substitution on memory is warranted (Beauchet, 2006;Gooren, 2007). To the best of my knowledge, researches describing the effect of testosterone on the histology and ultrastructure of the cells in the hippocampus were hardly found.…”
Section: Introductionmentioning
confidence: 99%